2016
DOI: 10.2147/ott.s93343
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in RAD51 and their relation with breast cancer in Saudi females

Abstract: The present study aimed at investigating the relationship between rs1801320 (G>C), rs1801321 (G>T), and rs2619681 (C>T) RAD51 gene polymorphisms and the risk of breast cancer development in Saudi females. The genotypes were analyzed using TaqMan genotyping assay and polymerase chain reaction-restriction fragment length polymorphism. The genotype and allele frequencies were computed using chi-square or Fisher’s exact test (two-tailed) by SPSS 21 software. The results showed that rs1801321G>T GG genotype and G a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…RAD51 polymorphism rs1801321; 172G>T is one of the most common polymorphisms located at the 5′UTR ( 26 ). In terms of clinical significance, rs1801321 has been linked with endometrial cancer ( 27 ) and there is a significant association with breast cancer ( 28 , 29 ). At the same time, a number of studies have suggested no association with ovarian cancer ( 30 , 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…RAD51 polymorphism rs1801321; 172G>T is one of the most common polymorphisms located at the 5′UTR ( 26 ). In terms of clinical significance, rs1801321 has been linked with endometrial cancer ( 27 ) and there is a significant association with breast cancer ( 28 , 29 ). At the same time, a number of studies have suggested no association with ovarian cancer ( 30 , 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…The 172 T allele-containing genotypes, on the other-hand, were found to be associated with some 25% reduction of general odds of cancer compared to the 172 GG wild-type one [10]. Nevertheless, association between 172 T allele and the risk of BrC seems to be much more complex, as only limited number of studies are available so far, suggesting both increase [25,26] as well as decrease [27,28] of the disease risk being associated with the allele, not allowing us thus to draw any final conclusion.…”
Section: Introductionmentioning
confidence: 99%
“…RAD51 is a key recombinase in the process of double-strand breaks (DSBs) repair by homologous recombination; other accessory proteins are involved in the DSBs such as RAD51 family proteins and breast cancer associated proteins BRCA1 and BRCA2 [10,11]. Genetic alteration in rad51 has been shown to be related to cancer development by several studies [12][13][14][15][16][17][18][19][20][21]. For instance, RAD51 and RAD51-related proteins have been found to be overexpressed and deregulated in some types of cancers like colorectal, pancreatic and breast cancers [22][23][24][25][26].…”
Section: Genetic Toxicology Introductionmentioning
confidence: 99%